Pemanfaatan Manajemen Pelayanan Surat Kantor Desa Gandasoli - Andina Dwijayanti; Pramesti, Puji; Rita Komalasari; Zen Munawar; Poniah Juliawati (Darma Abdi Karya, 2023)
This research aims to improve the weaknesses that exist in the manual correspondence management system at Gandasoli Village Office. The method used in this research is the waterfall system development method. The website-based letter management application created is intended to facilitate letter management at Gandasoli Village Office in terms of making letters, inputting data needed for making letters, printing letters and storing letters, managing incoming and outgoing letters, managing and grouping letter data that has been made based on the letter group, searching letters based on Letter Number and printing incoming and outgoing letter reports.